ETIKA DAN MORALITAS ORGANISASI PEMERINTAH - Ainur Ropik (Wardah, 2015)
Ethics inside of the organization is a pattern of attitudes and behaviors that are expected of every individual and group members of the organization , as a whole part will form the culture of the organization ( organizational culture) that is consistent with the goals and philosophy of the organization. Improving the ethical standards of government organizations actually lifts the quality of the embodiment or fulfillment behaviour values or norms and attitude in the policies and government actions , which can satisfy and build public trust . Because without public trust, all governments will not be able to run the government effectively and efficiently